Development Strategy for an Oyster Mushroom Business in Nueva Ecija, Philippines Using SWOT and Use Oyster Mushroom Business Or Oyster Mushroom Cultivation Business - Jomell M. Campos; Emmanuel N. Santiago (Journal of Economics Business Industry, 2024)
This study aims to formulate and prioritize development strategies for an oyster mushroom cultivation business located in Barangay Singalat, Muñoz, Nueva Ecija, Philippines. The business faces several problems, including declining production based on internal business records, limited production capacity, simple production facilities, short shelf life of fresh oyster mushrooms, weak financial recording, limited use of digital marketing, and failure to achieve sales targets. This study used a descriptive case study approach by combining SWOT analysis and TOPSIS. Data were collected through observation, business record review, and interviews with 10 purposively selected informants consisting of the owner, production workers, marketing personnel, customers, local agricultural officers, and agribusiness experts. The Internal Factor Evaluation matrix and External Factor Evaluation matrix were used to evaluate internal and external conditions. The IFE score was 3.056, indicating a strong internal position, while the EFE score was 2.991, indicating a moderate to high external response. The IE matrix placed the business in the growth and build position. SWOT analysis generated eight alternative strategies, which were then ranked using TOPSIS based on four criteria. After recalculation, the priority strategy was A4, namely creating educational and promotional social media content to attract customers, with a corrected closeness coefficient of 0.7853 under the assumption that implementation burden is treated as a cost criterion. The results indicate that digital promotion can be prioritized, but it must be supported by production planning, delivery readiness, financial recording, and product shelf life management. This study contributes to strategic decision making for small scale oyster mushroom agribusiness by integrating SWOT diagnosis with TOPSIS based priority ranking.